2005
DOI: 10.1111/j.1440-1681.2005.04254.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF ECONAZOLE ON Ca2+ LEVELS IN AND THE GROWTH OF HUMAN PROSTATE CANCER PC3 CELLS

Abstract: 1. Econazole is used clinically as an antifungal drug with many different in vitro effects. However, the effects of econazole on prostate cancer cells are unknown. The effects of econazole on intracellular Ca2+ concentrations ([Ca2+]i) in and the proliferation of human PC3 prostate cancer cells was explored in the present study using fura-2 and tetrazolium as fluorescent dyes. 2. At a concentration of 0.1 micromol/L, econazole started to increase [Ca2+]i in a concentration-dependent manner. The econazole-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
(42 reference statements)
2
20
0
Order By: Relevance
“…Fig. 8 , but it remains to be uncertain the type of channels implicated, as nifedipine, an L-type channels antagonist, failed to inhibit the entry, in clear connection with previous reports [28,29]. Moreover, a phospholipase D (PLD) pathway did not seem to be implicated in econazole response, as cells treated with propanolol failed to abolish the econazole response.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Fig. 8 , but it remains to be uncertain the type of channels implicated, as nifedipine, an L-type channels antagonist, failed to inhibit the entry, in clear connection with previous reports [28,29]. Moreover, a phospholipase D (PLD) pathway did not seem to be implicated in econazole response, as cells treated with propanolol failed to abolish the econazole response.…”
Section: Resultssupporting
confidence: 62%
“…Moreover, a phospholipase D (PLD) pathway did not seem to be implicated in econazole response, as cells treated with propanolol failed to abolish the econazole response. Concerning the stores implicated in the econazoleinduced Ca 2+ release, thapsigargin-sensitive stores proved to be econazole's target, as demonstrated for different cell lines [28,29]. U73122, a pharmacological inhibitor of PLC, significantly abolished the econazoleinduced rise in [Ca 2+ ] i .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the sensitivity of breast cancer cells to econazole could be enhanced 10-fold by concurrently stimulating them with epidermal growth factor or bombesin. Other groups have shown that prostate cancer cells (14) and colon cancer cells (13) are also sensitive to econazole. However, genetic or other factors associated with tumor cells that might regulate sensitivity to econazole have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%
“…1) presently under investigation for its anticancer effects. Econazole has shown cytotoxicity in several human cancer cell lines including breast cancer (3,4), osteosarcoma (5), PC3 prostate cancer cells (6), colon cancer (7) and myeloid leukemia cells (8,9). In this manner, econazole depletes cellular calcium stores and leads to inhibition of protein synthesis and cell death (1,2).…”
Section: Introductionmentioning
confidence: 99%